Gut microbiome regulation in equine animals: current understanding and future perspectives - Li, Fenglin; Kong, Xiangyu; Khan, Muhammad Zahoor; Wei, Lin; Wei, Jinjin; Zhu, Mingxia; Liu, Guiqin; Huang, Bingjian; Wang, Changfa; Zhang, Zhenwei (Frontiers in Microbiology, 2025)
The equine intestinal microbiome represents a complex and dynamic ecosystem that fundamentally influences host health and physiological function. This microbial community exhibits distinct compositional and functional variations across different anatomical segments of the intestinal tract, with diversity and abundance patterns shaped by host genetics, dietary inputs, and environmental conditions. The resident microbiota performs essential functions in feed fermentation, nutrient metabolism, pathogen exclusion, and immunological programming. This review synthesizes current knowledge regarding the core taxonomic and functional attributes of the equine intestinal microbiome, examining interspecies variation and conservation patterns. We evaluate key determinants of microbial community assembly and regulation, while examining mechanistic links between microbiota composition and host health outcomes. Through critical analysis of existing literature, this work provides an integrated framework for understanding the equine gut microbiome, with implications for clinical intervention strategies and evidence-based approaches to promote intestinal health in equine.